LITERATURE REVIEW: THE RELATIONSHIP BETWEEN STRESS AND EMOTIONAL EATING AMONG UNIVERSITY STUDENTS IN INDONESIA - Putri, Citta Nabila Rafida; Mandagi, Ayik Mirayanti (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2025)
Background: The prevalence of emotional mental disorders in adulthood has been increasing annually, with stress identified as a significant risk factor. Purpose: This study aims to investigate the correlation between stress and emotional eating among Indonesian university students. Methods: A systematic literature review was conducted using the PRISMA-P framework, analyzing relevant international and national articles from the Google Scholar database. Results: College students who experience stress have been shown to engage in emotional eating. Furthermore, emotional eating has been demonstrated to heighten the probability of obesity. Conclusion: The study confirms a significant correlation between stress levels and emotional eating behaviors among college students. Abstrak Latar belakang: Prevalensi gangguan mental emosional pada usia dewasa meningkat dari tahun ke tahun. Salah satu risiko terbesar penyebab gangguan mental adalah stres. Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan antara stres dengan emotional eating pada mahasiswa di Indonesia. Metode: Penelitian ini menggunakan metode systematic literature review artikel internasional dan nasional tentang hubungan stres dengan emotional eating pada mahasiswa di Indonesia yang dipublikasikan pada database Google Scholar yang menggunakan metode PRISMA-. Hasil: Mahasiswa yang mengalami stres cenderung mengalami emotional eating. Selain itu, emotional eating berdampak pada peningkatan resiko obesitas. Kesimpulan: Stres pada mahasiswa berhubungan dengan perilaku emotional eating.